Returning to Work After Spinal Cord Injury Are we "Investing in Regression"? - Mesquita, José Luís; Serviço de Medicina Física e de Reabilitação - Centro Hospitalar Universitário Lisboa Norte, Lisboa, Portugal. (2023)
Introduction: A successful return to work following spinal cord injury has well documented physical and psychological health benefits. Nevertheless, the percentage of people returning to work actually decreased over the years. This study aims to identify the impact of injury severity, functional impairment, time since injury onset, level of education and the need to readapt the job on returning to work following SCI.Methods: A telephone interview was conducted with individuals with spinal cord injury admitted to a rehabilitation center during 2015. Fifty one patients agreed to participate, corresponding to individuals aged between 15 and 66 years, with injuries that occurred between 1976 and 2015 who were professionally active prior to injury. Each participant was asked about their level of education, current employment, need of changing employer or entering vocational rehabilitation and period of time until returning to work. Information was collected from discharge summaries on injury etiology, American Spinal Injury Association Impairment Scale and Functional Independence Measure.Results: About half of the patients (n=26; 51%) returned to work after injury. It was found that individuals who return to work have a higher level of education (p=0.02). Keeping the same employer is also a facilitating factor, allowing a quicker return (p=0.002). On the other hand, individuals who do not return to work do not have more severe neurological injuries (p=0.21) or lower levels of functional independence (p=0.13) than those who remain professionally active. Also, those who have lived with the injury longer do not have higher rates of return to work (p=0.36).Conclusion: Despite the progressive development of multidisciplinary care in the rehabilitation of spinal cord injury patients, return to work is a complex and undefined process. Its success does not seem to be fully determined by the impact of motor, sensory, autonomic and psychosocial dysfunction. Thus, expectations are created in individualized vocational rehabilitation, which must be enhanced by measures to facilitate reentering labor market.